IL-6 and TNF-alpha polymorphisms in portuguese psoriatic patients - Ferreira, J.P. (2014)
Introduction: Cytokines regulate the growth, function and differentiation of cells and help to steer immune response and inflammation. In this study we focused our attention in two proinflammatory cytokines: IL-6 and TNFa. It is known that their overexpression is responsible for initiation, maintenance and recurrence of skin lesions in psoriatic patients. Therefore, it is important to investigate genetic biomarkers with functional effects in the genes of those cytokines that could help to predict the severity of Psoriasis. Objectives: To investigate the hypothesis that allelic variants in IL-6 and TNF-a genes are a risk factor for the developing of severe Psoriasis. Materials and Methods: A cohort of 178 (74 females, 104 males) psoriatic patients with severe plaque type psoriasis [according to the Psoriasis Area and Severity Index (PASI)] and 206 healthy individuals were selected. Several polymorphisms in the IL-6 gene (rs1800795, rs1800796, rs2069827, rs2069840) and TNF-a (rs361525, rs1799964, rs1800629) promoter region were genotyped. SNP genotyping was performed using Mass Spectrometry (MassARRAY iPLEX–Sequenom). Results: We observed a lower frequency in the minor allele (C) of the TNFa rs1799964 SNP in psoriatic patients, compared with controls [(21.9% vs. 29.4%), p = 0.02, OR = 0.675 (0.49–0.94)]. The frequency of the CC genotype in patients was 3.93% while in the healthy control group it was 9.22% [(p = 0.04, OR = 0.403 (0.17–0.98)]. No statistical significant differences were found in the other polymorphisms. Conclusion: Our data suggest that the rs1799964 C allele could be a protective factor for developing severe psoriasis. These results were similar to the findings of Gallo et al (2012) in a Spanish population. The mechanism to explain this association remains elusive, given the lack of evidence of a functional association.